Oxidative Stress Is Differentially Present in Multiple Sclerosis Courses, Early Evident, and Unrelated to Treatment - Maira Gironi; Bruno Borgiani; Enrica Mariani; Cristina Cursano; Laura Mendozzi; Rossella Cavarretta; Marina Saresella; Mario Clerici; Giancarlo Comi; Marco Rovaris; Roberto Furlan (Journal of Immunology Research)
Background. Oxidative stress is well documented in multiple sclerosis (MS) lesions, but its correspondence at peripheral level is still controversial. Objective. To evaluate peripheral oxidative stress markers in MS patients. Methods. We studied total blood levels of Coenzyme Q10 (CoQ10), oxidized and reduced forms of glutathione, malondialdehyde, reactive oxygen species (ROS), anti-oxidized-low-density lipoproteins (anti-oxLDL) antibodies, and antioxidant power (PAO) in 87 patients with different MS clinical phenotypes and in 77 controls. Results. CoQ10 was lower whereas anti-oxLDL antibodies titer was higher in MS patients than in controls. The benign variant of MS displayed both higher CoQ10 and higher anti-oxLDL than other MS clinical variants. Female patients had lower CoQ10 and PAO and higher ROS than male patients. Differences were greater in younger patients with shorter disease duration. Surprisingly, there was no difference for these markers between treated and untreated patients. Conclusion. We found lower antioxidant agents and higher anti-oxLDL antibodies in MS, and the highest antibody titers occurred in the benign form. We suggest that natural anti-oxLDL antibodies can be protective against MS, saving blood brain barrier integrity. Our findings also suggest that milder MS is associated with a distinct oxidative stress pattern, which may provide a useful biomarker of disease prognosis.